Representasi Nilai Kasih Sayang dalam Film “Ayat-Ayat Cinta” Karya Hanung Bramantyo - Ahmad Ahadiat; Alexi Sapta; Denti Listiana; Dadan Firdaus (Journal of Literature Review, 2026)
This study examines the representation of the value of compassion (rahmah) in the film Ayat-Ayat Cinta using Roland Barthes' semiotic theory. The film, adapted from Habiburrahman El Shirazy's novel, presents various forms of compassion through scenes and dialogues that carry layered meanings. This research analyzes signs at three levels: denotation, connotation, and myth. The findings reveal that compassion in the film is represented through social empathy, emotional sacrifice, patience in conflict, and spiritual love rooted in religious values. At the mythical level, the film reinforces cultural and religious ideals such as the concept of a devoted wife, a just husband, and the notion that true love transcends personal possession. These representations reflect Islamic values and Eastern cultural ideologies embedded in Indonesian society